KARAKTERISTIK SOSIS ANALOG DARI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DAN TEPUNG KACANG TOLO (Vigna unguiculata L.Walp) DENGAN BINDER PUTIH TELUR DAN FILLER TERIGU - , TIARATRI ADANINGGAR C.P.; , Ir. Sri Kanoni, M.S, ([Yogyakarta] : Universitas Gadjah Mada, 2013)
the most of people have a high risk awareness of food consume, not only Nowadays, the taste but also health, one of is decreased intake cholesterol of the body. One of decreased intake the cholesterol of body is vegetarian diet, which is not consume animal products like sausage. To supply the needs of variants diet for lacto ovo vegetarian, sausage can made from alternative materials such as oyster mushrooms with the addition of cowpea flour. The aim of this study is to know the ratio of oyster mushrooms and cowpea flour with white egg and wheat as binder and filter that liked by consumer, and also to know the sensory, physical, and chemical characteristic from the analogue sausage that produced. Analogue sausage produced by refer from Bologna imitation formula's with modification against material used that is oyster mushrooms and wheat flour with the ratio 0:100 , 25:75, 50:50, 75:25, and 100:0, and ratio of white egg and wheat 10:90, 20:80 and 30:70. Analogue sausage that being made then conducted sensory analysis to the preference and descriptive to decide ratio of oyster mushroom with cowpea flour and decide the appropriate ratio of egg white and wheat flour. Physical analysis which include the emulsion stability, cooking loss, color, chewiness, hardness, and microscopic emulsion with chemical analysis that consist by water content, protein, fat ,ash and carbohydrate by difference. The result of the research shows that variation of egg white and wheat flour don't give effect for sensory properties and physical of sausage analogue. The analogue sausage selected is analogue sausage with the ratio of oyster mushroom with cowpea flour 90:10 and egg white with wheat flour 20:80, with physical characteristic of emulsion stability is high (98,78%), low value of cooking loss (1,35%), value of L(brightness) 52,86, A(redness) 1,21, B( yellowness) 12,36, chewiness 26,51 (%of deformation), hardness 0,17 N, with chemical characteristic of water content is 59,21 (%wb), protein 11,10(%db), fat 27,94(%db), ash 7,75(%db), carbohydrate (by difference) 63,15(%db).